Factors affecting health care utilization of immigrants living in North of Turkey. Issue 1 (31st December 2020) - Korkmaz, Mehmet; Avci, Ilknur Aydın
Abstract : Purpose: This paper aims to determine factors affecting health-care utilization of immigrants living in North of Turkey and make a case assessment about this factors and general health status of immigrants. Design/methodology/approach: This study was conducted in accordance with the principles of descriptive research. The data of the study were collected by using questionnaire consisting of 33 questions that include socio-demographic specifications, use of health services and health perception level. Findings: This study was conducted with 360 immigrants. Participants, of which 61.9% were female. Immigrants who are young, female, married, have low education, have chronic illnesses, and have been in hospital before, have a better use of health services. Originality/value: Immigration experiences of immigrants and their lack of equal opportunities to access health services in the community lead them to use health services at a low level.